Prognostic value of neutrophil-to-lymphocyte ratio in patients with non–muscle-invasive bladder cancer with intravesical Bacillus Calmette–Guérin immunotherapy: a systematic review and meta-analysis - Huang, Jiaguo; Lin, Li; Mao, Dikai; Hua, Runmiao; Guan, Feifei (Frontiers in Immunology, 2024)
The predictive accuracy of the preoperative neutrophil-to-lymphocyte ratio (NLR) on the prognosis of non-muscle-invasive bladder cancer (NMIBC) patients with intravesical Bacillus Calmette-Guérin immunotherapy (BCG) after transurethral resection of the bladder tumor (TURBT) remains unknown. Therefore, the current study performed a systematic review and meta-analysis to examine the relationship between preoperative NLR and the prognosis of NMIBC patients with intravesical BCG immunotherapy.Methods: For this systematic review and meta-analysis, articles were was retrieved from PubMed, the Cochrane Library, Web of Science, and Embase databases from their inception to May 14, 2024.The role of NLR in predicting recurrence and progression in NMIBC was determined using pooled hazard ratios (HRs) and 95% confidence intervals (CIs).Results: Seven articles were included in this meta-analysis, involving 4,187 patients. An elevated NLR was significantly associated with recurrence (HR=2.67, 95% CI=1.34-5.32, P<0.001) and progression (HR=1.72, 95% CI=1.13-2.60, P =0.004) in NMIBC patients with intravesical BCG immunotherapy.This meta-analysis demonstrated that elevated preoperative NLR levels were significantly associated with recurrence and disease progression in NMIBC patients who underwent intravesical BCG immunotherapy after TURBT.